The Effect of Organizational Climate and Work Discipline on Employee Performance with Employee Commitment as an Intervening Variable - Rusady, Mitha Virgina; Rahmawati, Rahmawati; Fauzi, Achmad (Dinasti International Journal of Economics, Finance & Accounting, 2025)
As a way to see how corporate climate and work discipline affect employee success, this study uses employee commitment as a middle ground. An opinion poll of people working in local government offices was used as the quantitative method for this study. Closed-ended polls were used to collect data, and the Structural Equation Modeling (SEM) method was used to look at the results. The results showed that work environment and regulations have a large and positive influence on how well employees do their jobs. In addition, employee dedication successfully mediates the relationship between corporate atmosphere, work discipline, and performance, which makes the indirect effect stronger. The results of this study support theories of motivation and organizational commitment. They show how important it is to create a helpful workplace and encourage employees to be disciplined to increase productivity. Practically, this study emphasizes the importance for organizations to not only focus on managing the working environment and discipline, but also strengthening the psychological and emotional commitment of employees in the Central Balikpapan Sub-district Office. This research also shows the potential of applying this model in different types of organizations to extend the results.